CO-COMBUSTION EVALUATION OF SPENT BLEACHING EARTH AND COAL: A STUDY CASE IN CEMENT INDUSTRY - Lestianingrum, Erna; Bramantiyo, Ranoe; Nugraha, Maulana Gilar (ASEAN Journal of Systems Engineering, 2022)
As one of largest producers of greenhouse gas (GHG) emission, cement industries are committed to applying alternative ways to reduce the GHG emission level. Co-combustion of spent bleaching earth (SBE) and coal in cement industry is evaluated to reduce dependencies on fossil fuels. Such evaluation is conducted at one of cement plants in Indonesia owned by PT Indocement Tunggal Prakarsa Tbk. Palimanan Unit (PT ITP Palimanan Unit). Combustion in rotary kiln and calciner in two plant units (P9 and P10) were analyzed and compared. The comparison was conducted not only between plant units but also in different combustion operations, i.e., with and without SBE utilization as co-combustion agent. Several parameters consisting of temperature and gas compositions, which include CO, PM, SO2, NO2, CO2, and O2, were analyzed.The study results show insignificant differences in the kiln temperature, while in the calciner, SBE utilization enhances temperature level by up to 40°C compared to the process without SBE. Based on gas composition measurement, slight discrepancies are observed between the two different combustion conditions, although different trends in average absolute value are obtained. NO2 and PM concentrations are found to be slightly higher in the system without SBE, while an opposite trend is observed in SO2 emission. The study also discovered that properties of raw coal and SBE influence the emission trend in the combustion system. This work highlights the potential of SBE co-combustion with coal to be applied in a continuous manner since it provides slightly higher energy conversion while maintaining nearly similar emission level. In addition, the utilization of SBE is found to not cause significant disturbance to the rotary kiln and calciner operations.